The Effect of Plyometrics Exercise through Agility Ladder Drill on Improving Physical Abilities of 13–15-Year-Old Volleyball Players - Harry Pramono; Tandiyo Rahayu; Dewangga Yudhistira (Physical Education Theory and Methodology, 2023)
Study purpose. The purpose of this study was to test the plyometrics training method through agility ladder drills to increase leg muscle power, agility, and aerobic endurance in 13-15-year-old volleyball players.